The Effect of SiO2 Addition to the Hydroxyapatite/Curcumin Composite Properties - Windarti, Tri; Prasetya, Nor Basid Adiwibawa; Ngadiwiyana, Ngadiwiyana (Indonesian Journal of Chemistry, 2024)
Hydroxyapatite/curcumin composites have been studied as a calcium phosphate cement candidate. In this research, the effects of adding SiO2 to the hydroxyapatite/curcumin composite on the characteristics of the cement, such as the crystal and surface properties, as well as the release behavior of curcumin in Ringer's solution media, were studied. The composite preparation with and without SiO2 was carried out using a Na2HPO4 2.5% solution. The results showed that the addition of 25% SiO2 to the hydroxyapatite/curcumin composite did not change the crystal properties of hydroxyapatite but produced a more homogenous distribution of the ingredients. The behavior of the composite in Ringer's solution also changes, which is proven by the change in the crystal growth direction and Ca/P ratio. Adding SiO2 produced a composite with a platter and larger particles, as well as a higher Ca/P ratio on the surface. The presence of SiO2 inhibited the release of curcumin in which the ratio of HA: curcumin changed from 77.7%:22.3% to 69.6%:30.4% after 5 d of immersion in Ringer's solution. Thus, besides increasing calcium phosphate deposition on the cement surface, SiO2 also prevents curcumin from being released from the composite.